Russian Verb Aspects - Severyn, Nadiia (National Technical University "Kharkiv Polytechnic Institute", 2019)
Learner’s guide is intended for foreign students for beginners and advanced learners. Learner’s guide consists of four sections and includes informative tables and exercises. Learner’s guide can be used in Russian language lessons and independent work of foreign students.

Методические указания предназначены для иностранных студентов начального и продвинутого этапов обучения. Методические указания состоят из 4 разделов, включающих информативные таблицы и упражнения. Методические указания могут быть использованы на уроках русского языка, а также для самостоятельной работы иностранных студентов.
Виды русского глагола